Challenges of a small insular developing state : Cape Verde - Sarmento, Eduardo Moraes (2021)
The aim of the current study is to make the diagnosis of tourism in Cape Verde and point out major challenges to sustainable development in Cape Verde. To carry out this purpose, we conducted 19 in-depth interviews (22 April and 3 July 2019) with managers of di erent sector in Cape Verde. This number of interviews allow us to achieve the saturation. Cape Verde authorities should be aware that islands have lack of lodgings and infrastructures, small diversi cation of tourism products, high costs of water, energy, communications, and infrastructures as well as a limited quality of vocational training.